Digital mind maps (DMM) in developing students’ critical thinking within the course of Business Communication - Aimoldina, A.A.; Zharkynbekova, Sh.K. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2023)
In the era of information technology development, various interactive computer programmes and electronic resources in educational settings are of particular relevance for effective teacher-student interaction. This paper discusses didactic potential of using Digital Mind Mapping (DMM) technology in the context of developing Masters students’ critical thinking within business communication classes. In this context, mind mapping is an innovative strategy to facilitate recognition and memorization of important information by students, as well as to ensure the depth of their understanding by making connections between pieces of information and to develop critical thinking of students. The study gives an overview of services for creating DMM, a comparative analysis of their functional characteristics, and also offers a model for using DMM consisting of several stages, using the “Business communication” course in a foreign language for Masters students as an example. The authors concludes that the use of DMM in the educational process stimulates the development of creative abilities and critical thinking of students; develops general cultural competencies of students in group work; promotes the development of argumentation skills; justification of their point of view and possession of clear oral and written speech; forms the ability to work in a team, and promotes the development of cooperation skills; makes it possible to master the training material in an accelerated form; promotes the development of various types of memory.
Digital Mind Maps іскерлік коммуникация курсында студенттердің сыни тұрғыдан ойлауын дамыту
Digital Mind Maps в развитии критического мышления студентов в рамках курса деловой коммуникации
Keywords: mind maps; digital mind mapping; critical thinking; business communication; distance learning; business culture; visual aids; problem-based learning